2020
DOI: 10.1002/jper.19-0745
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between gingival bleeding and associated factors with reports of verbal bullying in adolescents

Abstract: Background Dentofacial features are related to increased bullying episodes in young people. The aim of this study was to assess the association between gingival bleeding and reports of verbal bullying among adolescents. Methods This is a cross‐sectional study conducted with a representative sample of 608 12‐year‐old adolescents from southern Brazil. The occurrence of verbal bullying was verified through adolescents' self‐report. Oral health measurements included the presence of gingival bleeding, dental fractu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 41 publications
1
11
0
1
Order By: Relevance
“…Previous studies have shown that factors related to the school environment are associated with OHRQoL [24,25]. In addition, oral health measures, such as dental shame, impact on the occurrence of dental bullying among schoolchildren [26]. In this context, as social distancing prevented daily contact among adolescents, it is believed that OHRQoL was less affected in this period, especially in the emotional well-being and social well-being domains, as demonstrated in our findings.…”
Section: Discussionsupporting
confidence: 68%
“…Previous studies have shown that factors related to the school environment are associated with OHRQoL [24,25]. In addition, oral health measures, such as dental shame, impact on the occurrence of dental bullying among schoolchildren [26]. In this context, as social distancing prevented daily contact among adolescents, it is believed that OHRQoL was less affected in this period, especially in the emotional well-being and social well-being domains, as demonstrated in our findings.…”
Section: Discussionsupporting
confidence: 68%
“…Indigenous children experience some of the highest levels of marginalisation in the world [60,75,76]. Experiences of racial discrimination may lead to parents not seeking dental healthcare for their children or waiting until only removing teeth is viable, and this may lead to bullying in school [16,[19][20][21][22][77][78][79].…”
Section: Discussionmentioning
confidence: 99%
“…Indigenous children experience some of the highest levels of marginalisation in the world [66,80,81]. Experiences of racial discrimination may lead to parents not seeking dental healthcare for their children or waiting until only removing teeth is viable, and this may lead to bullying in school [17,[20][21][22][23]82,83].…”
Section: Discussionmentioning
confidence: 99%